Effects of the thyristor controlled serie capacitor on the electric power system - Colman, Luiz Ricardo Sanches [UNESP]; De Araujo, Percival Bueno [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
This work deals with the effects of the series compensation on the electric power system for small-signal stability studies. Therefore, the system is modeled admitting the existence of the compensation and then, the equations are linearized and a linear model is obtained for a single machine-infinite bus power system with a compensator installed. The resulting model with nine defined constants is very similar to the Heffron & Phillips linear model widely used on the existent literature. Finally, simulations are executed for an example system, to analyze the behavior of these constants when loading the system. © 2004 IEEE.
Keywords: Electric Power Systems; FACTS; Linear Models; Power System Stability; Series Compensator; Small-signal Stability; Linear models; Power system stability; Series compensator; Small-signal stability; Capacitors; Electric lines; Electric potential; Electric power systems; Integration; Investments; Lyapunov methods; Signal processing; Vectors; Thyristors